PUISI “LOLO MA YAMME” ‘INGAT KAMI’ TELAAH IDEOLOGI KULTURAL - Alex Djawa (Jurnal Lazuardi, 2020)
This poem is written, as a form of concern, disappointment, frustration, resentment, anger over the mindset, behavior, habits, and actions that burden and impoverish them all. Everything they have, such as land, fields, and rice fields, is sold out for useless purposes such as traditional parties, deaths and funerals, pulling stones, building traditional houses, and so on. The education of children and grandchildren is not even ignored. Generations of children and grandchildren encourage their ancestors and parents to hear complaints and hopes for their future. They expect to be sent to school to change their future which is still very long. They expect their ancestors to pass on to them an intelligent and great generation. They expect God to help and bless them.